Evolusi Kepemimpinan : Mengungkap Dinamika Kepemimpinan Berbasis Nilai di Perguruan Tinggi - Agnes Renostini Harefa; Desman Telaumbanua; Rosnelli Rosnelli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to identify the main themes that emerge in leadership practice in higher education and how applying these values can affect leader behaviour, organizational culture, and the quality of education. The method used in this research is content analysis. Content analysis is a widely used qualitative research technique that allows the examination of various forms of media to identify patterns, themes, and meanings associated with value-based leadership in higher education. The research data source comes from publication articles or research reports on leadership in higher education. Conclusion of this study: Value-based leadership implemented in higher education includes servant, transformational, transactional and collective-colegial leadership. The evolution of leadership directs that leadership in higher education needs to adapt to changes in the global environment, technology, and societal demands. Leadership evolution involves transitioning from traditional approaches to more participatory, innovative techniques. This leadership approach leads to an inclusive and value-based leadership model and a transformative and innovation-based leadership model. Keywords: Leadership Evolution, Values, Transformative, Inclusive